Scouring downstream of overflowing weir - Lin, Yi Han. (2011)
Experiments with varying flowrates, apron lengths and tailwater depths were conducted to investigate the scour hole formation downstream of an overflowing weir with and without an apron. The effect of median grain size of the sediment bed is also studied by comparing the data obtained in this project with those by another similar study but of a different grain size.The results showed that the maximum equilibrium scour depth increases when flowrate increases, tailwater depth decreases, apron length decreases, and grain size decreases. A modified “predetermined equilibrium scour rate” method is used to determine the maximum equilibrium scour depth dse and equilibrium scour time te. Using dimensional and regression analysis, predictive equations are also proposed for the dimensionless forms of dse and te in terms of Δ 2, 2, 50 2 and . The computed and measured values of the equations agreed well with an error range of ±15%. An equation on the effect of apron length on scour is also proposed which shows that scour can be reduced by 60% or more once the apron length is more than 1.5 times the height of the weir structure